Optimalisasi Pelayanan Publik Berbasis Digital Di Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Sinjai - Ihsan Ihsan; Mursak Mursak; Salman salman (Universitas Mbojo Bima, 2025)
The digitalization of public services is a strategic step by the government to improve efficiency and service quality for society. This study aims to analyze the implementation of digital-based public services at the Department of Population and Civil Registration (Disdukcapil) of Sinjai Regency, identify supporting and inhibiting factors, and formulate optimization strategies based on empirical data. This research employed a descriptive qualitative approach through in-depth interviews, participatory observation, and document review. The findings indicate that the adoption of digital systems such as the Population Administration Information System (SIAK), Online Dukcapil, and Dukcapil Self-Service Kiosk (ADM) has facilitated easier access for the public. However, limited technological infrastructure, human resource competencies, and digital literacy remain major challenges. Supporting factors include regulatory frameworks, leadership commitment, and growing public demand. Optimization strategies include capacity building for human resources, strengthening IT infrastructure, digital literacy education, and developing more adaptive and integrated service systems.